INTERNATIONAL LAW AND FINANCE AS THE MEANS OF REDUCING THE RISK OF DISASTERS AND CATASTROPHES - Sarsembayev Марат Алдоңғарұлы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2023)
This article is dedicated to the ways and methods by which international law and finance could contribute to reducing the risks of disasters. The author of this article attempts to reconcile international law and finance with new Kazakh laws of financial and legal nature, which he proposes to develop and adopt, with a view to effectively contribute to reducing the risks of disasters throughout Kazakhstan, includin